Mitigating aflatoxin in Rwanda - Herrman, T.J.; Hoffmann, Vivian; Kamaraba, I.; Konlambigue, Matieyedou (Texas A&M University, 2021)
On August 18th, 2021, the International Growth Centre and the Rwandan Ministry of Agriculture organised a webinar under the theme Market Driven Strategies for Mitigating Aflatoxin in Rwanda. The webinar highlighted Rwanda's progress towards mitigating aflatoxin and showcased innovative approaches used by neighbouring countries. The event was an opportunity for stakeholders to discuss Rwanda’s key challenges in post-harvest management and assess the evidence on approaches that have (not) worked in similar contexts.